Influence Policy Tax, Tax Administration, Loopholes, and Tax Rates to Effectiveness Management Member Company Tax of HIPMI in Batam - Taufan Maulamin; Vonnicia Vonnicia (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
This study discuss about how much influence from policy tax, tax administration, loopholes and tariffs tax to effectiveness management tax company on each owned company every HIPMI members in Batam City. Object study this is companies registered with HIPMI. Destination from study this is for now and evaluate how much big influence policy tax, tax administration, loopholes and tariffs tax by together to effectiveness management tax company HIPMI members in Batam City. Method research used is Descriptive quantitative. Data collection through deployment questionnaire, with amount population of 223 companies registered with HIPMI in Batam City whereas sample on research this taken with formula slovin and amounted to 69 respondents. Data analysis using analysis regression multiple. Research results show that variable of policy tax take effect positive and significant by 20.8% against effectiveness management tax company, then variable of tax administration take effect positive and significant by 32.2% against effectiveness management tax company, then loopholes variable effect positive and significant by 37.7% against effectiveness management tax company, and variable rate tax take effect positive and significant by 61.8% against effectiveness management tax company, as well as variable of policy tax, tax administration, loopholes and tax rates by simultaneous take effect positive and significant by 91% against effectiveness management tax companies that can see of R square (R2) or the test of determination.